A rapid stability indicating LC-method for determination of praziquantel in presence of its pharmacopoeial impurities - Hisham Hashem; Adel Ehab Ibrahim; Magda Elhenawee (Arabian Journal of Chemistry, 2017)
This study reports for the first time about a stability indicating RP-HPLC method for quantitative determination of Praziquantel (PZQ) in bulk powder and dosage form and in presence of its pharmacopoeial impurities. The chromatographic separation was carried out on (Caltrex AI®) calixarene column, a relatively new packing material. Chromatography was done using an isocratic binary mobile phase consisting of ACN and 25 mM ammonium acetate (NH4Ac) in the ratio of 40:60 at flow rate of 1 mL min−1, 30 °C and 210 nm wavelength for detection. The elution time of PZQ was found to be 6.15 ± 0.03 min. The method was validated for system suitability, linearity, precision, limits of detection and quantitation, specificity, stability and robustness. The robustness study was done for small changes in temperature, flow rate, wavelength of detection and % of ACN in mobile phase. Stability tests were done through exposure of the analyte solution to five different stress conditions: Reflux with 1 N HCl, reflux with 1 N NaOH, reflux with 30% H2O2, thermal degradation of powder and exposure to UV radiation. Limits of detection and quantification were found to be 0.56 and 1.70 μg mL−1, respectively. The recovery value of this method was 100.30% ± 1.10 and the reproducibility was within 1.31.